Circling faith southern women on spirituality - Reed, Wendy; Horne, Jennifer; Adams, Mitzi; Awiakta, Marilou; Blackmarr, Amy.; Chapman, Marshall; Cushman, Susan; Fennelly, Beth Ann.; Fowler, Connie May.; Gibson, Margaret; Johnson, Rheta Grimsley; Karr, Mary.; et al. (Tuscaloosa : University of Alabama Press, 2012)
Circling Faith is a collection of essays by southern women that encompasses spirituality and the experience of winding through the religiously charged environment of the American South. Mary Karr, in & ldquo;Facing Altars, & rdquo; describes how the consolation she found in poetry directed her to a similar solace in prayer. In & ldquo;Chiaroscuro: Shimmer and Shadow, & rdquo; Susan Cushman recounts how her dissatisfaction with a Presbyterian upbringing led her to hold her own worship services at home and eventually to join the Eastern Orthodox Church. & ldquo;Magic & rdquo; by Amy Blackmarr depicts.
What the Body Knows -- Barbara Brown TaylorThe Queen of Hearts -- Margaret Gibson; IV. Questioning Life Without Faith?; Rapture on Hold -- Rheta Grimsley Johnson; The Only Jews in Town -- Stella Suberman; A Purposeful Life -- Mitzi Adams; V. Transforming Faith in Change; A Fairy Tale: The Prodigal Daughter Returns -- Connie May Fowler; Alice Walker Calls God "Mama": An Interview with Alice -- Valerie Reiss; Signs of Faith -- Barbara Robinette Moss; What We Will Call Nature -- Cia White; Contributors; Permissions.
Description based on print version record.
Keywords: Faith; Women -- Religious life -- Southern States; Spirituality; Women authors -- Religious life; Faith; Southern women -- Religious life; Spirituality; Women authors -- Religious life; Religion; RELIGION / Religious Intolerance, Persecution & Conflict; Electronic books